Development and Psychometric Evaluation of Fluoride Acceptance Scale in Turkish Language - Tuncer, Kevser; Ataş, Osman (My University, 2024)
Objective: The use of fluoride is one of the few evidence-based preventive of dental caries. Fluoride rejection is a growing public health concern. Public health researchers need to develop fluoride rejection screening tools, diagnostic tools, and evidence-based strategies for optimal preventive dental care decisions. This study aimed to develop a Fluoride Acceptance Scale (FAS). Material and Method: Six hundred and sixty-two volunteers were included for the research. An item pool consisting of 15 items was developed as a result of literature review. A 6-point Likert Scale ranging from 0 to 5 was used in this scale. Four items were removed at the content validity stage and one item at the internal consistency stage. Internal consistency stage 10 of them were accepted for the scale based on Cronbach's Alpha values. The mean Content Validity Indeks value of the scale was calculated as 0.95. The data were analyzed using SPSS Statistics Pack version 22.0 (IBM, Armonk, NY). Results: In this study, Turkish Fluoride Acceptance Scale was developed to measure fluoride acceptance. The scale consisted of 10 questions and 2 factors: A: Fluoride Benefit and Protection (6 questions), B: Opposition to Fluoride (4 questions). The Cronbach's Alpha was 0.862, Kaiser-Mayer- Olkin was 0.826. Factor load values of all items (10 items) were found to be 0.5 and above. Conclusion: The FAS can be used to assess fluoride acceptance in an easy and quick way and can assist in the development of health policies.
Keywords: Pediatric Dentistry; Preventive Dentistry; Scale; Fluoride; Community dentistry